PELAKSANAAN PROMOSI OBJEK WISATA TABEK PABOUN DI DESA PEBAUN HILIR KECAMATAN KUANTAN MUDIK - Rinauman, Arezky; Ibrahim, Mariaty (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Developing tourism potential in Tabek Paboun, Pebaun Hilir Village, Kuantan Mudik District, Riau Province. Using qualitative descriptive methods, this research explores the implementation of promotions through Personal Selling, Mass Selling, Sales Promotions, Public Relations, and Direct Marketing. The research results show that although Tabek Paboun has a unique natural tourist attraction, challenges such as limited infrastructure, budget, and lack of community participation in promotion are the main obstacles. This research suggests increasing accessibility, diversifying tourist attractions, and empowering local communities to maximize tourism potential while improving the local economy. Keywords: Tabek Paboun, Tourism Promotion, Marketing Strategy, Sustainable Tourism, Tourism Village.